RANCANG BANGUN SISTEM PAKAR UNTUK DETEKSI DINI TINGKAT DEPRESI PASCA MELAHIRKAN (Universitas (STKIP) PGRI Sumatera Barat, 2022)
Information technology is currently developing very rapidly, one of which is in the health sector. Current computer/machine technology, which is equipped with various capabilities, is able to recognize the human condition, one of which is related to human psychological health. Psychological health often appears in post-natal women; not a few women experience stress and even depression, some women manage to adjust well, but others fail to adjust and experience psychological disorders with various symptoms. Technological innovations that are currently able to carry out early detection of various diseases or psychological disorders in humans, one of which uses an expert system designed from expert knowledge to help diagnose early symptoms of a psychological disorder or a disease. At the data collection stage, interviews, observations, and documents related to psychological disorders that occur in postpartum women will be carried out, and this activity will involve experts, in this case, the midwife. Psychological disorders that often occur in postpartum women are divided into three based on the level of disturbance, and the first is Post Partum Blues, Post Partum Depression, and Post Partum Psychosis. Data on symptoms of psychological disorders were obtained from the results of data collection. The data obtained in the form of symptoms of psychological disorders that are often encountered in the field, in this case, the practice of midwives, the data will be processed so that manual trials can be carried out on the methods used. Application development is carried out using the System Development Life Cycle (SDLC) model or the system development life cycle. The SDLC model that will be used is the waterfall method where this method is systematic sequential in building software. The general stages in the waterfall method are requirements analysis, system design, system implementation, and the last is system testing. The implementation of this expert system application will use the Certainty Factor (CF) method.